Genetic variability of early flowering and yield contributing traits in Barnyard Millet [Echinochloa frumentacea (Roxb). Link] grown at different altitudes (Indian Journal of Experimental Biology (IJEB), 2022)
Barnyard millet is an important up surging minor millet in Asia countries for food and nutritional security. Being a minorcrop, the genetics and inheritance of the traits need to understand, for effective utilization in the crop improvementprogrammes. Here, we investigated the genetic background and inheritance of different traits in barnyard millet genotypes.Forty germplasm accessions were evaluated in different ecological environments of southern India for 17 quantitative traits.Genetic variability analysis using GENSTAT and the pooled REML mean data results revealed that Phenotypic Co-efficientof Variation (PCV) was greater than the Genotypic Co-efficient of Variation (GCV) over the diverged ecological locationsindicating the existence of environmental influence on all the biometric traits studied. In the Western Ghats region (E1),high heritability coupled with high genetic advance was exhibited for traits like days to flowering, plant height, days tomaturity, number of nodes, length of nodes, number of basal tillers, stem diameter, flag leaf length, flag leaf width,inflorescence length, inflorescence width, length of peduncle, number of racemes, single ear head weight and grain yield perplant. Traits like thousand grain weight expressed moderate genetic advance with high heritability while, length of lowerracemes expressed moderate heritability with high genetic advance. Similarly, high heritability coupled with high geneticadvance was recorded for all the characters in valley region (E2) except thousand grain weight that showed high heritabilitybut moderate genetic advance. In contrast, in the area of plains (E3), all the traits exhibited high heritability coupled withhigh genetic advance. Since, majority of the traits have shown high heritability with high genetic advance, selection mightbe effective in these traits irrespective of the environment.